Chemical modulation of the metabolism of an endophytic fungal strain of Cophinforma mamane using epigenetic modifiers and amino-acids. Issue 5 (May 2022) - Pacheco-Tapia, R.; Vásquez-Ocmín, P.; Duthen, S.; Ortíz, S.; Jargeat, P.; Amasifuen, C.; Haddad, M.; Vansteelandt, M.
Abstract: Endophytic fungi are capable of producing a great diversity of bioactive metabolites. However, the presence of silent and lowly expressed genes represents a main challenge for the discovery of novel secondary metabolites with different potential uses. Epigenetic modifiers have shown to perturb the production of fungal metabolites through the induction of silent biosynthetic pathways leading to an enhanced chemical diversity. Moreover, the addition of bioprecursors to the culture medium has been described as a useful strategy to induce specific biosynthetic pathways. The aim of this study was to assess the effects of different chemical modulators on the metabolic profiles of an endophytic fungal strain of Cophinforma mamane (Botryosphaeriaceae), known to produce 3 thiodiketopiperazine (TDKP) alkaloids (botryosulfuranols A-C), previously isolated and characterized by our team. Four epigenetic modifiers, 5-azacytidine (AZA), sodium butyrate (SB), nicotinamide (NIC), homoserine lactone (HSL) as well as 2 amino acids, l -phenylalanine and l -tryptophan, as bioprecursors of TDKPs, were used. The metabolic profiles were analysed by UHPLC-HRMS/MS under an untargeted metabolomics approach. Our results show that the addition of the two amino acids in C. mamane culture and the treatment with AZA significantly reduced the production of the TDKPs botryosulfuranols A, B and C. Interestingly, the treatment with HSL significantly induced the production of different classes of diketopiperazines (DKPs). The treatment with AZA resulted as the most effective epigenetic modifier for the alteration of the secondary metabolite profile of C. mamane by promoting the expression of cryptic genes.